Frequency of MB2 Canals in Maxillary First Permanent Molars - Mehmood Ahmed Rana, Anam Akram, Mohammad Tahir, Khurram Nadeem, Ammar Abdullah Malik, Syed Usama Shayan Zaidi, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The primary objective of this doctoral-level study was to investigate the prevalence and anatomical variations of the second mesiobuccal (MB2) canals in maxillary first permanent molars, thereby contributing to the enhancement of endodontic treatment outcomes. Study Place and Duration: The research was conducted at the Bakhtawar Amin Medical and Dental College Multan, with a study duration of 12 months (January 2022 to December 2022). Study Design: This investigation employed a cross-sectional, observational study design, meticulously examining maxillary first permanent molars in a diverse patient population. Methods: A total of 400 extracted maxillary first permanent molars were collected and analyzed using cone-beam computed tomography (CBCT) scans and dental operating microscope (DOM). Samples were categorized by age, gender, and ethnicity. The teeth were accessed, and MB2 canals were detected through a combination of clinical and radiographic methods. The prevalence and variations of MB2 canals were evaluated, and data were statistically analyzed using chi-square and Fisher's exact tests, with a significance level set at p<0.05. Results: The overall prevalence of MB2 canals in the investigated sample was 67.5% (n=270). A strong association between the presence of MB2 canals and age (p<0.001) was observed, with a higher prevalence among younger patients. No significant difference was detected concerning gender (p=0.33) or ethnicity (p=0.17). Various anatomical variations of MB2 canals were identified, with Vertucci's Type II configuration being the most common (40%). Conclusion: The findings underscore the significance of thorough exploration and accurate identification of MB2 canals during endodontic procedures on maxillary first permanent molars. The observed high prevalence and diverse anatomical variations of MB2 canals necessitate meticulous attention to enhance the success of endodontic treatments. Keywords: MB2 canals, maxillary first permanent molars, endodontics, cone-beam computed tomography, dental operating microscope, anatomical variations, prevalence, Vertucci's classification.